Microestructura y propiedades mecánicas de una soldadura disímil AL6XN-INCONEL 600 - Paz Zavala, Francisco (Universidad Michoacana de San Nicolás de Hidalgo, 2019)
In this work was studied the effects of the microstructure and mechanical properties of the application of low intensity magnetic field of 3 mT during the dissimilar welded of plates AL6-XN / IN600 made by means of the welding process with gas protection (mixture of Ar-3% N? and Ar-3% N?-2% N?) and with consumable metallic electrode (GMAW, for its acronym in English). 6.35 mm thick plates were cut from the base materials AL-6XN and Inconel 600, they were prepared in simple V. They were welded with inverted polarity using the electrodes ERNiCrMo3 and ER310 of 1.2 mm in diameter. The operational variables of the welding process were adjusted to produce a heat of contribution between 1.05 to 1.15 kJ / mm in a single pass. The microstructural characterization of the welds revealed a refining effect of grain when welding with the application of magnetic field and counteracted the growth of columnar grains. The interaction of the low intensity magnetic field had no effect on the dilution of the welded joints, in addition the non-mixing zone at the interface between the welding zone and the base material AL-6XN was reduced for both electrode to the degree of not being completely visible along the fusion lines. When welding with magnetic field the hardness in the ZAT on the side of the IN600 in the welded joint with the ERNiCrMo3 electrode with magnetic field was reduced and those of the base materials increased, while with the ER310 electrode the hardness in both the base materials and in the cord increased due to the effect of the low intensity magnetic field.

En este trabajo se estudiaron los efectos en la microestructura y propiedades mecánicas de la aplicación de campo magnético de baja intensidad de 3 mT durante la unión disimíl de placas AL6-XN/IN600 realizada por medio del proceso de soldadura con protección de gas (mezcla de Ar-3% N? y Ar-3% N?-2% N?) y con electrodo metálico consumible (GMAW, por sus siglas en inglés). Se cortaron placas de 6.35 mm de espesor de los materiales base AL-6XN e Inconel 600, se les dio una preparación en simple V. Se soldaron con polaridad invertida utilizando los electrodos ERNiCrMo3 y ER310 de 1.2 mm de diámetro. Las variables operativas del proceso de soldadura se ajustaron para producir un calor de aporte entre 1.05 a 1.15 kJ/mm en una sola pasada. La caracterización microestructural de las soldaduras reveló un efecto de refinamiento de grano al soldar con la aplicación de campo magnético y contrarrestó el crecimiento de granos columnares. La interacción del campo magnético de baja intensidad no tuvo efecto en la dilución de las uniones soldadas, además la zona de no mezcla en la interfaz entre la zona de soldadura y el material base AL-6XN se redujo para ambos electrodos al grado de no ser completamente visible a lo largo de las líneas de fusión. Al soldar con campo magnético la dureza en la ZAT del lado del IN600 en la unión soldada con el electrodo ERNiCrMo3 con campo magnético se redujo y las de los materiales base aumentaron, mientras con el electrodo ER310 la dureza tanto en los materiales base como en el cordón aumentaron por efecto del campo magnético de baja intensidad.
Instituto de Investigación en Metalurgia y Materiales. Maestría en Metalurgia y Ciencias de los Materiales
Keywords: info:eu-repo/classification/cti/7; IIMM-M-2019-0292; GMAW; ZAT; Campo magnético; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5320